The role of strategic planning in improving the performance of public education departments in Makkah, in light of the Kingdom of Saudi Arabia’s 2030 vision - Alzahrani, Abdulaziz Saleh Mohammed (Journal of Economic, Administrative and Legal Sciences, 2020)
This study aimed to identify the weaknesses and shortcomings in the level of strategic planning in the public education departments in Makkah region and how to overcome them, to improve their performance in light of the Kingdom of Saudi Arabia 2030 vision. The study used the descriptive analytical approach on documents, and the tool was to refer to books, researches, studies and specialized literature on the subject of research, and the research consists of three main chapters, the first chapter dealt with the general framework of the research, and the second: the theoretical framework and previous studies, As for the third chapter, it includes the conclusion, recommendations and proposals. The results showed the importance of strategic planning in improving the performance of public education departments and the performance of their employees, in addition to many benefits that ultimately lead to the quality of education outcomes, which have become an urgent necessity; required by the current stage, to ensure the achievement of the Kingdom of Saudi Arabia 2030 vision, and to maintain its leadership position regionally and globally. In light of the results, a set of recommendations and proposals were presented: to activate the strategic planning methodology to improve the performance of educational departments and schools in Makkah and other regions throughout the Kingdom.